PROGRAM ANALYSIS OF COST-VOLUME-PROFIT ANALYSIS SENSTIVITAS FOR PLANNING BY USING TURBO PASCAL - Suci Lestari; Jalinas Jalinas, SKom, MM (Jurnal Sistem Informasi, 2002)
With increased competition in the world economy many companies use variousmethods to remain current business developments in the modern era.Use cost-volume-profit as one method for the management to plan the number ofproducts will be sold with care existing factors, such as the competitive situation onthe acceptance or rejection of the consumer against price increases, fixed costincreases are expected for ad inc rease the volume of sales, variable costs down ifpossible, or a combination of these factors.From analysis above problem we can use sensitivity analysis so that all the planningthat has been created to run as expected.